2015
DOI: 10.1152/ajpregu.00048.2015
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity interval and endurance training are associated with divergent skeletal muscle adaptations in a rodent model of hypertension

Abstract: Skeletal muscle is extremely adaptable to a variety of metabolic challenges, as both traditional moderate-intensity endurance (ET) and high-intensity interval training (HIIT) increases oxidative potential in a coordinated manner. Although these responses have been clearly demonstrated in healthy individuals, it remains to be determined whether both produce similar responses in the context of hypertension, one of the most prevalent and costly diseases worldwide. Therefore, in the current study, we used the Dahl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Mitochondrial function is composed of two factors: mitochondrial respiratory capacity for the organelle itself; and the absolute volume fraction of mitochondria within a given cell. Furthermore, specifically relevant to muscle one must also consider the muscle fiber type composition since the mitochondrial fraction varies considerably between cell types and has been suggested as an adaptive mechanism in some metabolic diseases . Mitochondrial function is important in metabolic disease since MOP drives substrate utilization and skeletal muscle can account for up to 80% of glucose uptake .…”
Section: Mitochondrial Function and Skeletal Muscle Metabolism In Metmentioning
confidence: 99%
“…Mitochondrial function is composed of two factors: mitochondrial respiratory capacity for the organelle itself; and the absolute volume fraction of mitochondria within a given cell. Furthermore, specifically relevant to muscle one must also consider the muscle fiber type composition since the mitochondrial fraction varies considerably between cell types and has been suggested as an adaptive mechanism in some metabolic diseases . Mitochondrial function is important in metabolic disease since MOP drives substrate utilization and skeletal muscle can account for up to 80% of glucose uptake .…”
Section: Mitochondrial Function and Skeletal Muscle Metabolism In Metmentioning
confidence: 99%
“…At present, whether HIIT in the setting of hypertension provides a beneficial or detrimental intervention is highly controversial (32,35). Indeed, although significant evidence suggests that HIIT is beneficial in a wide range of cardiovascular disorders (31)(32)(33), others have posited that it may, in fact, provide a detrimental stimulus that promotes a pathologic state specific to hypertension (35)(36)(37). Although we cannot resolutely refute the latter argument, our current data provide strong evidence that HIIT is associated with significant beneficial adaptations in hypertension, as related to improvements in diaphragm function, endothelial function, and exercise tolerance.…”
Section: Effects Of Hiit On Diaphragm Dysfunction In Hypertensionmentioning
confidence: 99%
“…In particular, HIIT has been touted as the most beneficial exercise intervention for patients with cardiovascular disease (31)(32)(33), providing superior benefits in the skeletal muscle compared with traditional endurance training (34). In contrast, however, recent evidence has suggested that HIIT induces a pathologic state in hypertension (35,36) that also has deleterious effects on skeletal muscle (37). Therefore, it remains controversial whether HIIT is conducive or detrimental in the setting of hypertension, with more evidence needed to support or reject either of these hypotheses.…”
mentioning
confidence: 99%
“…Our laboratory has provided evidence that in a rodent model of hypertension, ET had overall beneficial effects in both skeletal (Holloway et al . a ) and cardiac muscle (Holloway et al . b ), while in contrast HIIT did not.…”
Section: Exercise As a Secondary Prevention Toolmentioning
confidence: 99%
“…Specifically, in skeletal muscle, HIIT promoted a transition towards a more glycolytic phenotype and a reduced capillary‐to‐fibre ratio (Holloway et al . a ). In cardiac muscle, ET protected against LV hypertrophy and fibrosis, and promoted increased LV capillary‐to‐fibre ratios; however, HIIT promoted pathological adaptations in the LV of hypertensive rats (Holloway et al .…”
Section: Exercise As a Secondary Prevention Toolmentioning
confidence: 99%